Rejuvenation techniques for revival of the senile and old almond (Prunus dulcis) orchard in north western Himalaya region - SRIVASTAVA, K K; AHMAD, N; KUMAR, DINESH; BHAT, S K (The Indian Journal of Agricultural Sciences, 2015)
An experiment was conducted during 2009-11 at CITH, Srinagar, J&K to standardized the rejuvenation techniques in old and senile almond (Prunus dulcis (Mill) DA Webb) orchard. Highest graft success and number of laterals were recorded in P2 pruning level and the F1 fertilizer dose resulted highest linear growth of laterals and graft success. Water harvesting structure W1 resulted highest linear growth (52.25 cm), number of laterals (10.47) and graft success (27.73%). The V1 (Waris) variety resulted highest graft success among the varieties. The treatment combination P3F1W1V1 resulted highest canopy area (2.85 m2), however, the nut yield (1.94 kg/tree) was noted in P1F1W1V1 treatment combinations.